Intra-tumoral lymphocyte scoring in colorectal cancer: improving prognostic utility and correlation with underlying cancer biology - Wagner, Patrick L.; Xie, Jianwu; Flaherty, Devin C.; Park, Hyun; Knotts, Chelsea; Debelius, Justine; Tilves, Curtis; Dadgar, Neda; Xiao, Kunhong; Zaidi, Ali H.; Acevedo, Louis Gil; LaFramboise, William; et al. (Frontiers in Gastroenterology, 2024)
BackgroundIntra-tumoral lymphocytes hold prognostic and predictive significance in colorectal cancer (CRC). The internationally validated Immunoscore™ predicts CRC survival risk by averaging percentile scores of tumor-associated CD3+ and CD8+ cell densities, but is limited by increased cost, intra-tumoral heterogeneity and omission of other immunologic variables of importance. To address these limitations, we sought to explore alternative prognostic markers based on CD3+ and CD8+ quantification in CRC.Methods201 resected CRCs were subjected to quantitative CD3/CD8 immunohistochemistry, from which percentile cell counts were averaged (“I-score”) in a manner analogous to the Immunoscore™. I-score and exploratory endpoints, including CD3+ and CD8+ cell densities/percentiles, CD3+-CD8+ density/percentile differences, and CD3+:CD8+ density/percentile ratios were tested for association with clinicopathologic and genomic correlates and disease-specific survival (DSS).ResultsCD3+ density among CRCs was right-skewed and potentially bimodal, while CD8+ density was right-skewed. Density and intra-tumoral variability for CD3+ and CD8+, as well as combination metrics including I-score, CD3+-CD8+ density/percentile differences, and CD3+-CD8+ density/percentile ratios showed distinct clinicopathologic and genomic associations, suggesting that each may hold unique biological significance. CD3+ density, CD8+ density/percentile, I-score and CD3+:CD8+ percentile ratio were associated with DSS; only CD3+:CD8+ percentile ratio was pTNM stage-independent on multivariable analysis. Independently, CD8+ density was as prognostic as I-score, questioning the necessity of CD3, or a combination metric.ConclusionsI-score, in our study, was closely associated with potentially confounding biologic variables such as sex, active smoking, pTNM stage, and mutations in BRAF, and MMR genes. More precise and biologically relevant biomarkers can be achieved by using data-driven CD3+/CD8+ density cutoffs and ratios, while controlling for important clinicopathologic and molecular variables in CRC. Independent validation and inclusion of other relevant immunocyte types could bring these findings closer to clinical utility in CRC.